Global Health Trade Summit: an AI-enhanced simulation of international trade and global health for undergraduate public health education - Patil, Uday; Terada, Melissa; Nelson-Hurwitz, Denise C. (Frontiers in Public Health, 2025)
IntroductionThe Global Health Trade Summit is an undergraduate classroom activity designed to help students understand the role of international trade in addressing population health needs, especially given recent news about trade disruptions, health inequities, and access challenges. This economic simulation incorporates experiential learning and a constructivist pedagogical style, best practices in undergraduate public health pedagogy.MethodsThis card game activity, designed with the assistance of artificial intelligence tools OpenAI ChatGPT and Adobe Firefly, involved gathering historical news and economic data, resource allocation, outcome simulation, and image generation. It aligns with objectives outlined in the guidelines for public health education set forth by CEPH, ASPPH, and CUGH. Pilot testing of the activity was facilitated by an instructor and teaching assistant with 39 students in an introductory global health course.ResultsStudents fully participated and remained engaged throughout the pilot activity, which closely mirrored resource management and trading mechanics prevalent in popular board and card games. The pandemic context resonated with them, enhancing their comprehension of international trade and its associated macroeconomic concepts, such as international aid, supply chain disruptions, and resource distribution challenges. Students reported enjoying the activity and provided valuable suggestions for enhancing the simulation’s effectiveness.DiscussionThe success of the pilot activity underscores the value of engaging economic games in public health instruction. These activities are facilitated or enhanced through the utilization of readily available artificial intelligence tools for education. Recommendations for other instructors are also provided, along with opportunities for research.